Influencia de la concentración del sedimento fino en el gradiente hidráulico para flujo de agua en tuberías a presión. - Vásquez, L. (2023)
The hydraulic transport of sediments in circular conduits that work under pressure is subject to changes in the flow conditions that basically affect the pressure losses due to friction and therefore the hydraulic gradient of the flow, which depends on the concentration of suspended sediments. . In this sense, in the present work, the dependence of the sediment concentration of the water-fine sediment mixture on the hydraulic gradient of the flow was analyzed, for which experimental laboratory tests were carried out, in Polyvinyl Chloride (PVC) pipes with diameters nominal values of ½”, 1” and 1 ½” for ML-type water-sediment mixtures (clayey silts), with concentrations by weight (Cw) of 1%, 3%, 5% and 7%, taking as baseline the flow for clear waters (Cw=0%). In this sense, it is evident that there is a positive linear correlation between the flow velocity of the water-sediment mixture and the hydraulic gradient (Sf) for all the concentrations studied, also fulfilling that for the same flow velocity at a higher concentration of fine sediment. in the greater mixture is the hydraulic gradient and vice versa. On average, the increase in the hydraulic gradient generated by the flow of mixtures of water with fine clayey silt sediment with concentrations of 1%, 3%, 5% and 7% for flow speeds between 0.9 m/s to 1.8 m/s in PVC pipes , is fulfilled: for 1/2" diameter it goes from 14% to 128%, for 1" diameter pipe it goes from 37% to 373% and for 1 ½" diameter pipe it goes from 68% to 811%, increments measured on the baseline of the hydraulic gradients of the flow with clear waters. Since water pipes are not always made for clear water, it is necessary to replicate this research with other types of sediments.